TRACKS ACROSS AFRICA ANOTHER TEN YEARS - CRAIG BODDINGTON (USA SAFARI PRESS, 2008)
Tracks Across Africa, which chronicles the author's third decade of African hunting. Pretty much every country open to hunting in this period saw Craig Boddington walking on its soil: C.A.R., Chad, Cameroon, Zimbabwe, Namibia, Tanzania, South Africa, Ethiopia, and Mozambique.
Keywords: HUNTING-AFRICA